Judias, brasileiras e mulheres : os caminhos para a construção de uma identidade feminina diaspórica entre as imigrantes judias na revista Corrente (1945-1963) - Rotta, Helen Rocha (2022)
The identity formation of Jewish women in the Brazilian diaspora is a topic that has not yet been explored. On the one hand, the historiography on the subject is still restricted and on the other hand, the community is still studied only in a general way, without a more attentive cut to the history of women. Attention is drawn to the debate that Jewish women establish in the political field, actively discussing the construction of democracy in Brazil, in the world and especially in Israel, the fall of authoritarian systems and especially about German totalitarianism, the revealed traumas of the Shoah and, above all, the way in which this political context can interfere in the elaboration of their worldviews. These political elements are understood as structuring the identity of Jewish women and especially located in their previous experiences in Europe in their regions of origin. The present research aims to analyze the identity formation of Jewish women in the Brazilian diaspora, based on their narratives written in a periodical of the time called Revista Corrente. Since this magazine is a publication of WIZO (Womens International Zionist Organization), it was possible to perceive the construction of meanings and worldviews of Jewish women in Brazil and the way in which they were interconnected with the most current debates of the Jewish world identity.